GEOLOGI DAN SUMBERDAYA BATUBARA DAERAH SATIUNG – KUALA KUAYAN DAN SEKITARNYA, KABUPATEN KOTAWARINGIN TIMUR, PROVINSI KALIMANTAN TENGAH - Rizal, Yan; Fahmi, Muhammad Agung Akrom; Haq, Hamzal Imanul (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Geological mapping on a scale of 1:25.000 was held in Satiung – Kuala Kuayan and its surrounding, East Kotawaringin, CentralKalimantan. The goal of this study is to identify the geological setting and coal potential in the research area. Primary data used in this research obtained from field observation and field data collection, such as outcrop data and drilling data. The stratigraphy of research area is divided into three unofficial units from the oldest to the youngest: Basement (Mesozoic), Dahor Formation (Pliocene – Pleistocene) and Alluvial. Coal quality of the study area shows lignite to sub-bituminous rank, with total resources is 291.737.730,9 Ton (measured 95.928.991,0 Ton and indicated 195.808.739,9 Ton).